2016
DOI: 10.53597/remim.v0i0.912
|View full text |Cite
|
Sign up to set email alerts
|

Morbidite Et Mortalite Chez Les Enfants De 01 a 59 Mois Hospitalises Au Service De Pediatrie Generale Du Chu Gabriel Toure De Janvier a Decembre 2013

Abstract: Objectif : Ce travail visait à étudier la morbidité et la mortalité chez les enfants âgés de 01 à 59 mois hospitalisés dans le service de pédiatrie générale du CHU Gabriel Touré.Matériels et Méthodes : Il s'agissait d'une étude rétrospective, descriptive, sur une période de 12 mois allant du 1er  janvier au 31 décembre 2013.Résultats : Nous avons inclus 1625 enfants âgés de 01 à 59 mois soit 58% des patients hospitalisés. Le tiers des patients avait moins d'un an. Les garçons représentaient 57 % de notre échan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Mali [29]. The predominance of early childhood in our series and in other countries with limited income is probably due to a greater susceptibility of this age group to killer infections in children, to the martial deficiency that is rampant in certain regions of the world, to malnutrition and to precarious socioeconomic conditions, as well as to the lack of vaccination [30].…”
Section: Age and Sexmentioning
confidence: 58%
“…Mali [29]. The predominance of early childhood in our series and in other countries with limited income is probably due to a greater susceptibility of this age group to killer infections in children, to the martial deficiency that is rampant in certain regions of the world, to malnutrition and to precarious socioeconomic conditions, as well as to the lack of vaccination [30].…”
Section: Age and Sexmentioning
confidence: 58%
“…Inadequate food intake (in terms of both quality and quantity) is at the root of development. This result is lower than those of Coulbaly M's 96.2% marasmus and 2.8% kwashiorkor [12] and Keita's 83% ma-Open Journal of Pediatrics rasmus and 10% kwashiorkor [5]. Maiga et al's study found similar results: 73.74% marasmus and 11.87% kwashiorkor [13].…”
Section: Discussionmentioning
confidence: 71%
“…The main causes of infant and child mortality in Benin are represented by malaria, acute respiratory tract infections, diarrhea, measles and malnutrition. 2 According to Doumbia et al 3 in Mali, the three main causes of child death were: malnutrition (47%), malaria (32%) and acute respiratory tract infections (19%).…”
Section: Introductionmentioning
confidence: 99%